Microwave synthesis of blue emissive N-doped carbon quantum dots as a fluorescent probe for free chlorine detection - Melissa Asha Larsson,; Pravena Ramachandran,; Purim Jarujamrus,; Lee, Hooi Ling (Penerbit Universiti Kebangsaan Malaysia, 2022)
Blue emissive N-doped carbon quantum dots (N-CQDs) were prepared through a convenient and sustainable microwave synthesis method using citric acid monohydrate (CA) and urea as carbon and nitrogen sources, respectively, with an optimum molar ratio of 1:3 (CA:Urea). The surface functional groups, morphology, and hydrodynamic characteristics of N-CQDs were analysed with Fourier-transform infrared (FTIR) spectroscopy, high-resolution transmission electron microscopy (HRTEM) and dynamic light scattering (DLS), respectively. The as-synthesised N-CQDs with a quantum yield of 14.8%, exhibited excitation-independent fluorescence emission at 443 nm due to surface-state-induced fluorescence, with an optimum excitation wavelength at 360 nm. The N-CQDs were spherical, with an average particle size of 7.29 ± 3.91 nm based on HRTEM analysis. However, DLS analysis showed that the hydrodynamic size (293.0 ± 110.8 nm) was larger than the average particle size due to the presence of hydrophilic polymer chains and abundant surface groups on the N-CQDs. The free chorine-induced fluorescence quenching of N-CQDs at pH 9 denotes the sensitivity of N-CQDs towards detection of free chlorine in the form of hypochlorite (ClO-) ion, providing the limit of detection (LOD) of 0.4 mM and limit of quantification (LOQ) of 1.2 mM. The fluorescence quenching effect in the N-CQDs caused by the quencher (ClO-) is attributed to the dynamic quenching mechanism, via an intersystem crossing. The low selectivity of N-CQDs towards various ions justified N-CQDs’ selectivity as a free chlorine fluorescent probe that can be used for wastewater testing due to its high range sensitivity.